2016
DOI: 10.1016/j.hkpj.2015.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Transverse oscillatory pressure in management of cervical radiculopathy: A randomised controlled study

Abstract: Background: Cervical radiculopathy is an important subgroup of neck disorders causing severe pain and disability. Objectives: The study assessed the effect of transverse oscillatory pressure (TOP) on pain intensity and functional disability of patients with cervical radiculopathy. Methods: Twenty-six individuals with unilateral radiating neck pain were randomly allocated into Group A (8 males and 5 females) and Group B (6 males and 7 females)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…It has been reported that spinal manual therapy such as VOP may excite polymodal nociceptors and wide dynamic range neurons that stimulate the release of opioid peptides such as enkephalin and morphins (Egwu et al, 2012). These opioid peptides in the central nervous system are proposed to be a factor in the analgesic effect of VOP (Ojoawo et al, 2016). Vertical oscillatory pressure tend to produce emotions driven by the aversive primary motive system which according to Egwu et al (2012) activates the amygdala and periaquiductal gray (PAG) area which release enkephalins and endorphins to modulate pain.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that spinal manual therapy such as VOP may excite polymodal nociceptors and wide dynamic range neurons that stimulate the release of opioid peptides such as enkephalin and morphins (Egwu et al, 2012). These opioid peptides in the central nervous system are proposed to be a factor in the analgesic effect of VOP (Ojoawo et al, 2016). Vertical oscillatory pressure tend to produce emotions driven by the aversive primary motive system which according to Egwu et al (2012) activates the amygdala and periaquiductal gray (PAG) area which release enkephalins and endorphins to modulate pain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…VOP is observed to be a painful procedure capable of causing anxiety which may lead to changes in respiratory mechanism (Ojoawo et al, 2016). Stress perceived by the patient during the application of a manual therapy treatment technique may account for the reported findings of sympathoexcitation and hypoalgesia immediately after its application (Egwu et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations